Mobile Mediated Listening Skill Instruction Effects on Students’ Listening Comprehension and Motivation - Kereba, Engliz Ketema (Edukasi, 2024)
The study investigated mobile-mediated listening instruction (MMLI) effects on students’ listening comprehension and motivation. Quasi-experimental non-randomized groups’ pre-test-post-test research design was adapted. Two groups with 30 students were considered as experimental group and control group. MMLI approach was applied to the experimental group, and conventional approach was used to teach the control group. Tests and questionnaires were employed to collect quantitative data. Statistical tools such as independent sample t-test, paired samples t-test, chi-square, and Spearman’s rho correlation were computed for the analysis. The results showed that MMLI approach had a strong and significant effect on students’ listening comprehension. A statistically significant difference was confirmed between the experimental and control groups in terms of their listening comprehension and motivation levels. There was a positive and statistically significant relationship between achievement and motivation of the two groups, with a strong effect size. It was concluded that the MMLI approach is an alternative in mediating students’ listening skills learning and increasing their motivation. Mobile technology is the opportunity to reconsider listening skills instruction in the technological era. Besides, M-learning platform package that incorporates text, audio, and tasks is believed to be designed to make students learn listening skills in their own time and pace.